Analisis Kinerja Non-Performing Loan (NPL) Bank Studi Kasus Bank BRI Tbk Cabang X - Muhammad Nur Abdi (Journal of Research in Business, Economics, and Education, 2021)
During the Covid-19 pandemic, it had a huge impact on the economy, especially the banking industry, which has experienced many obstacles in the past two years. Declining economic activity, rising inflation and changes in interest rates have caused banks to be very selective in anticipating and overcoming the surge in the non-performing loan (NPL) ratio. A high NPL is an indicator of a bank's failure to manage its business. The purpose of this study is to analyze the performance of banking NPLs, especially BRI Tbk branch X. The results obtained that the NPL ratio of Bank Rakyat Indonesia Branch X for four years (2016-2019) fluctuated every year, the average percentage of risk level of Bank Rakyat Indonesia branch X was 1.30%. This means that the Non-Performing Loan (NPL) of PT. Bank Rakyat Indonesia branch X for the four-year period (2016-2019) is low, and below the standards set by Bank Indonesia.